2010
DOI: 10.1002/ejic.201000162
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Uranyl Salts from Dialkylimidazolium Ionic Liquids or Their Precursors

Abstract: The interaction of uranyl nitrate hexahydrate with three ionic liquids and one ionic liquid precursor with minimal solvent addition led to the isolation and crystallographic characterization of four new uranyl salts: bis(1,3‐dimethylimidazolium) bis‐μ‐hydroxo‐bis[bis(nitrato‐O,O)dioxouranate(VI)], bis(1‐ethyl‐3‐methylimidazolium) bis‐μ‐hydroxo‐bis[bis(nitrato‐O,O)dioxouranate(VI)], bis(1,2,3‐trimethylimidazolium) bis‐μ‐hydroxo‐bis[bis(nitrato‐O,O)dioxouranate(VI)], and bis(1‐ethyl‐3‐methylimidazolium) trichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…As explained in this paper introduction, only one attempt 31 34 This hypothesis was not discussed by the authors, although the analyzed solutions were rather concentrated in uranium (0.4 M). Moreover, it has been shown that nitrates ions are stronger complexant to uranyl than water in hydrophobic IL, 35 so that the residual water in solution should not be able to compete with a massive concentration of nitrates for the uranyl complexation.…”
Section: -mentioning
confidence: 99%
“…As explained in this paper introduction, only one attempt 31 34 This hypothesis was not discussed by the authors, although the analyzed solutions were rather concentrated in uranium (0.4 M). Moreover, it has been shown that nitrates ions are stronger complexant to uranyl than water in hydrophobic IL, 35 so that the residual water in solution should not be able to compete with a massive concentration of nitrates for the uranyl complexation.…”
Section: -mentioning
confidence: 99%
“…In general, linkage of Ur(X m O n ) 5 polyhedra may proceed not only via edge-but also via corner-sharing. Cs 2 (UO 2 )(NO 3 )Cl 3 is the first purely inorganic uranyl oxohalide containing triangular NO 3 groups strongly bonded to Ur(X m O n ) 5 polyhedra (see also [7,8]). Further systematic attempts of hydrothermal synthesis of new alkali uranyl halides using halides of the heavier alkali metals (K, Rb, Cs) halides in excess as starting materials may lead to the discovery of new structure types with potentially interesting applications.…”
Section: Discussionmentioning
confidence: 99%
“…18 The geometrical features of structures (Tables S2−S6, Supporting Information) were calculated with Mercury 3.1 software (Cambridge Crystallographic Data Centre, Cambridge, UK). Hirshfeld Surface Analysis.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…Compounds with [(UO 2 ) 2 (μ-OH) 2 (NO 3 ) 4 ] 2− anions have been extensively studied with various countercations, such as imidazolium, 18,20 ammonium, 74 and pyridinium. 75 The compound 1 [Bmim] + cations with G′T and TE′ conformations, which maintain specific cation−anion interactions (Table S3, Supporting Information), could be compared with previous well-illustrated structures 18 (Table S3, Supporting Information). As shown in Figure 2b, the [Bmim] + cation with the G′T conformation formed one C− H···O bri , one C−H···O fre , and two C−H···O coo .…”
Section: Crystal Growth and Designmentioning
confidence: 99%
See 1 more Smart Citation